Repeat Procedures After Hybrid Thoracoscopic Ablation in the Setting of Longstanding Persistent Atrial Fibrillation: Electrophysiological Findings and 2‐Year Clinical Outcome. (13th November 2015) - VELAGIC, VEDRAN; DE ASMUNDIS, CARLO; MUGNAI, GIACOMO; IRFAN, GHAZALA; HUNUK, BURAK; STROKER, ERWIN; HACIOGLU, EBRU; UMBRAIN, VINCENT; BECKERS, STEFAN; CZAPLA, JENS; WELLENS, FRANCIS; NIJS, JAN; et al.
Lessons Learned from the Hybrid Redo Procedures: Introduction: In order to increase success rates of invasive treatment of persistent atrial fibrillation, the hybrid approach was developed, combining video‐assisted thoracoscopic epicardial procedure with conventional endocardial catheter ablation. Currently, there are no reports of electrophysiological findings and clinical outcomes of repeat procedures after the hybrid approach. Methods and Results: Out of 64 patients who were treated by hybrid ablation for persistent atrial fibrillation (AF), 14 underwent the repeat catheter ablation and were selected for this study. All 14 patients initially presented with longstanding persistent atrial fibrillation and markedly dilated atria. The hybrid procedure was performed in a single act and the mean time to redo procedure was 346 ± 227 days. In 57% of patients indication for redo procedure was regular atrial tachycardia, and the rest presented with recurrent atrial fibrillation. In 36% of patients, recovered conduction was found along the previous ablation lesions. Only 9% of pulmonary veins were reconnected (0.36 veins per patient) and 7% of box lesions were not complete. The overall success rate at 2 years follow‐up after the repeat procedure, including second repeat procedure and patients taking antiarrhythmic drugs, was 64% (57% without drugs and further ablation). One case of moderate pulmonary vein stenosis was detected as a consequence of hybrid procedure. Conclusion: Hybrid atrial fibrillation ablation results in durable lesions and high rates of chronic pulmonary vein isolation even after long‐term follow‐up. Most of the repeat procedures after the hybrid approach are related to left atrial flutters that could be successfully treated by catheter ablation.